Thin layer drying kinetics of Gundelia tournefortii L. - Evin, Duygu (Elsevier, 2012)
The literature surveyed revealed that the drying kinetics of Gundelia tournefortii has not been investigated. In this study, mathematical modeling of the thin layer drying kinetics of G. tournefortii is investigated for both the microwave and open sun drying conditions. Five different microwave power levels ranging from 90 to 800W were used for the microwave drying. Solar radiation for the open sun drying varied from 350 to 1100 W/m(2). Drying took place in the falling rate period. Increasing the microwave power caused a significant decrease in drying time. The experimental moisture loss data wee fitted to the 14 thin layer drying models. Among the models proposed, the Midilli model precisely represented the microwave drying behavior of G. tournefortii with the coefficient of determination higher than 0.996 and mean square of deviation (chi(2)), root mean square error (RMSE) and mean bias error (MBE) lower than 1.82 x 10(-4), 12 x 10(-3) and 1.4 x 10(-4), respectively for all the microwave drying conditions studied. Values of drying constant (k) were in if e range of 0.0098-0.2943 min(-1) and the effective moisture diffusivities (D-eff) of G. tournefortii ranged from 5.5 x 10(-8) to 3.5 x 10(-7) m(2)/s. The values of k and D-eff increased with the increase of microwave power level. The logarithmic model was found to best describe the open sun drying kinetics of G. tournefortii. The effective diffusivity of G. tournefortii under the sun drying condition was determined as 2.48 x 10(-10) m(2)/s. (C) 2011 The Institution of Chemical Engineers. Published by Elsevier B.V. All rights reserved.
Keywords: Gundelia tournefortii L.; Thin layer drying models; Microwave drying; Open sun drying; Drying kinetics